El hablador, de Mario Vargas Llosa, o la búsqueda infructuosa del Otro - Susti Gonzales, Alejandro Enrico (2018)
The Storyteller, by Mario Vargas Llosa, published in 1987, suggests throughout its pages a project of ethnographic fictionalization consisting on “making talk” a character of the Machiguenga culture —"the storyteller"—, by staging certain mechanisms of orality raised by Walter Ong for the so-called primary oral cultures. This paper examines these mechanisms as well as the displacement made by the author in order to have a more authentic fictionalization of the protagonist: Raúl Zuratas. This displacement and attempt of acculturation, however, is signaled by the marks of a speech strongly rooted in the Western tradition —making reference to art, literature or to the Christian literary tradition—, which invalidates the original purpose of ethnographic fiction as a product of the cultural distance established between writing and orality, and the impossibility of situating the character beyond History.